Research on Deep-Site Failure Mechanism of High-Steep Slope under Active Fault Creeping Dislocation - Yang Liu; Kaiwen Zhang; Denghang Tian; Liming Qu; Yang Liu (Shock and Vibration)
The reverse thrust in the deep site causes the upward propagation of stress and displacement in the overlying soil. The displacement field around the fault zone is maximum. As the spatial location becomes shallower, the soil displacement gradually becomes smaller. The deformation of the overlying soil is mainly affected by the vertical dislocation of the fracture zone. The monitoring curve showed no abrupt change value, indicating that the top surface of soil did not rupture, and only the influence of fault on the displacement transfer of the top surface of the soil. When a creeping dislocation occurs in the bottom fracture zone, the maximum principal stress of the upper boundary of the deep site is dominated by compressive stress. The maximum principal stress of the soil on both sides of the fracture zone has a maximum value, and the soil on the right side of the fracture zone has a significant compression effect. The maximum principal stress monitoring curve varies greatly, indicating the plastic failure development of soil, which is the same as the research results of the plastic failure zone in the following paper. When the bottom fracture zone starts to move, the plastic zone first appears at the junction area between the front end of the bottom fracture zone and the overlying soil. As the amount of dislocation of the fracture zone increases, the plastic zone continues to extend into the inner soil. The left and right sides of the fracture zone show tensile failure and compression failure, respectively. The development of the upper envelope curve in the plastic zone of the overlying soil satisfies the Boltzmann equation with a first-order exponential growth, while the development of the lower envelope curve satisfies the Gauss equation with a second-order exponential growth. The development curve equation of the plastic zone is verified according to the residual figures of the fitting result and the correlation parameters.